2013
DOI: 10.5772/51323
|View full text |Cite
|
Sign up to set email alerts
|

Stabilized Feedback Control of Unicycle Mobile Robots

Abstract: In this paper, a stabilized feedback control is designed for a class of unicycle non-holonomic mobile robots. The approach is based on kinematic polar coordinate transformations. The suggested control scheme allows the robot to achieve stabilized nearoptimal trajectories, while satisfying the hard constraints of specified initial and final postures (positions and orientations). Simulation experiments showing the effectiveness of the proposed technique are provided and discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Similarly to [16,17], we investigate a collective system of N identical autonomous mobile robots whose respective equations of motion are [15] qi…”
Section: Problem Formulationmentioning
confidence: 99%
“…Similarly to [16,17], we investigate a collective system of N identical autonomous mobile robots whose respective equations of motion are [15] qi…”
Section: Problem Formulationmentioning
confidence: 99%
“…Our aim is to construct a robust feedback controller, which makes system (1) asymptotically stable. More precisely, for a given known stabilizing control for the nominal system of (1), we want to redesign another robust stabilizing feedback control of the perturbed system (1). We can realize that we want to robustify an existing feedback control of the nominal system.…”
Section: Problem Statementmentioning
confidence: 99%
“…In the literature of the wheeled mobile robot control, there are two fundamental problems: posture stabilization and trajectory/path tracking. The aim of posture stabilization is to stabilize the robot to a desired point [1], while the trajectory tracking is to enforce the robot to follow a reference trajectory [2]. For WMRs, it is difficult to control such system by continuous time-invariant controller.…”
Section: Introductionmentioning
confidence: 99%
“…Discontinuous state feedback control laws have been proposed such as in Astolfi (1995), who suggested applying a single coordinate transformation to the non-holonomic system in chained form. Amar and Mohamed (2013) designed a controller based on kinematic polar coordinate transformations. D' Andrea-Novel et al (1991) showed that stabilization of three-wheel mobile robots is possible with static state feedback using Lagrange formalisms and differential geometry.…”
Section: Introductionmentioning
confidence: 99%